Platform Randomised trial of INterventions against COVID-19 In older peoPLE (PRINCIPLE): protocol for a randomised, controlled, open-label, adaptive platform, trial of community treatment of COVID-19 syndromic illness in people at higher risk - Hayward, G; Butler, CC; Yu, L-M; Saville, BR; Berry, N; Dorward, J; Gbinigie, O; van Hecke, O; Ogburn, E; Swayze, H; Bongard, E; Allen, J; et al. (BMJ Publishing Group, 2021)
Introduction There is an urgent need to idenfy treatments for COVID-19 that reduce illness duration and hospital admission in those at higher risk of a longer illness course and complications. Methods and analysis The Platform Randomised trial of INterventions against COVID-19 In older peoPLE trial is an open-label, multiarm, prospective, adaptive platform, randomised clinical trial to evaluate potential treatments for COVID-19 in the community. A master protocol governs the addition of new interventions as they become available, as well as the inclusion and cessation of existing intervention arms via frequent interim analyses. The first three interventions are hydroxychloroquine, azithromycin and doxycycline. Eligible participants must be symptomatic in the community with possible or confirmed COVID-19 that started in the preceding 14 days and either (1) aged 65 years and over or (2) aged 50–64 years with comorbidities. Recruitment is through general practice, health service helplines, COVID-19 ‘hot hubs’ and directly through the trial website. Participants are randomised to receive either usual care or a study drug plus usual care, and outcomes are collected via daily online symptom diary for 28 days from randomisation. The research team contacts participants and/or their study partner following days 7, 14 and 28 if the online diary is not completed. The trial has two coprimary endpoints: time to first self-report of feeling recovered from possible COVID-19 and hospital admission or death from possible COVID-19 infection, both within 28 days from randomisation. Prespecified interim analyses assess efficacy or futility of interventions and to modify randomisation probabilities that allocate more participants to interventions with better outcomes. Ethics and dissemination Ethical approval Ref: 20/SC/0158 South Central - Berkshire Research Ethics Committee; IRAS Project ID: 281958; EudraCT Number: 2020-001209-22. Results will be presented to policymakers and at conferences and published in peer-reviewed journals. Trial registration number ISRCTN86534580.